Hexokinase and Glucokinases Are Essential for Fitness and Virulence in the Pathogenic Yeast Candida albicans - Laurian, Romain; Dementhon, Karine; Doumèche, Bastien; Soulard, Alexandre; Noel, Thierry; Lemaire, Marc; Cotton, Pascale (Frontiers in Microbiology, 2019)
The pathogenic yeast Candida albicans is both a powerful commensal and pathogen of humans that can infect wide range of organs and body sites. Metabolic flexibility promotes infection and commensal colonization by this opportunistic pathogen. Yeast cell survival depends upon assimilation of fermentable and non-fermentable locally available carbon sources. Physiologically relevant sugars like glucose and fructose are present at low level in host niches. However, because glucose is the preferred substrate for energy and biosynthesis of structural components, its efficient detection and metabolization are fundamental for the metabolic adaptation of the pathogen. We explored and characterized the C. albicans hexose kinase system composed of one hexokinase (CaHxk2) and two glucokinases (CaGlk1 and CaGlk4). Using a set of mutant strains, we found that hexose phosphorylation is mostly assured by CaHxk2, which sustains growth on hexoses. Our data on hexokinase and glucokinase expression point out an absence of cross regulation mechanisms at the transcription level and different regulatory pathways. In the presence of glucose, CaHxk2 migrates in the nucleus and contributes to the glucose repression signaling pathway. In addition, CaHxk2 participates to oxidative, osmotic and cell wall stress responses, while glucokinases are overexpressed under hypoxia. Hexose phosphorylation is a key step necessary for filamentation, that is affected in the hexokinase mutant. Virulence of this mutant is clearly impacted in the Galleria mellonella and macrophage models. Filamentation, glucose phosphorylation and stress response defects of the hexokinase mutant prevent host killing by C. albicans. By contributing to metabolic flexibility, stress answer response and morphogenesis, hexose kinase enzymes play an essential role in the virulence of C. albicans.